Pengembangan Kurikulum PAI Berbasis Cinta Melalui Tafsir Al-Qur’an Untuk Penguatan Empati dan Regulasi Emosi - Hujjatul Fakhrurridha; M. Abdul Rohman; Mira Fathimatul 'Alimah; Akmalun Najmi; Hana Rusmalia; Sonia Isna Suratin (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
Social changes in the digital era trigger psychological and moral problems in students, including decreased empathy, impulsivity, and weak emotional regulation. This condition requires strengthening the Islamic Religious Education (PAI) curriculum that not only emphasizes cognitive aspects, but also fosters affective character based on the values ​​of love in the Qur'an. This study aims to formulate a love based PAI curriculum development model using an Al-Qur'anic interpretation approach as a strategy to strengthen empathy and emotional regulation in students in the digital era. The research method uses a qualitative approach with a type of library research, which examines classical and contemporary tafsir books, educational psychology literature, and PAI curriculum policy regulations. Data collection techniques include literature documentation, thematic analysis of Al-Qur'anic verses on love, compassion, empathy, and emotional control, and a comparative study of curriculum development models. Data are analyzed through reduction, categorization, and meaning drawing, and validated using theory and source triangulation to ensure the credibility of the interpretation. The research results show that the values ​​of love in the Quran, reflected in the concepts of mercy, compassion, kindness, and compassion, can be incorporated into an effective Islamic Religious Education curriculum designed in an integrated manner, encompassing objectives, materials, learning strategies, and evaluation. Based on the study of interpretation, this approach focuses on strengthening students' empathy, emotional awareness, and emotional regulation skills. Its implementation is carried out through reflective, dialogical learning, and the provision of role models relevant to the dynamics of student development in the digital era.